2019
DOI: 10.34050/els-jish.v2i4.8050
|View full text |Cite
|
Sign up to set email alerts
|

Development of Work Sheets for Students (LKPD) in Writing Explanation Text

Abstract: This study aims to describe the results of product trials based on the development of needs analysis results and product validation results that have been assessed. The product developed was LKPD in writing explanatory texts for high school students. This research is part of research and development (R&D) research. The method used in this research is qualitative and quantitative. Products are tested on students on a small scale. The product was tested on a class XI student of SMA Dharma Loka Pekanbaru. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Penelitian sebelumnnya menunjukkan bahwa belajar melalui bahan ajar dengan konten budaya memberikan pengalaman belajar yang lebih sehingga peserta didik merasa memiliki nilai-nilai budaya tersebut (Baka, 2019). Upaya memperkuat ketahanan budaya di Indonesia, guru memerlukan bahan ajar kontekstual untuk memberikan pengalaman belajar pada peserta didik (Charlina & Septyanti, 2019). Penggunaan LKPD bermuatan kearifan lokal merupakan penggunaan media belajar yang kontekstual yang bertujuan menciptakan sumber belajar yang layak untuk dipergunakan peserta didik dalam upaya meningkatkan ketahanan budaya lokal daerah melalui peningkatan pemahaman konsep kearifan lokal siswa dan pengalaman belajar siswa dari proses belajar di sekolah.…”
Section: Pendahuluanunclassified
“…Penelitian sebelumnnya menunjukkan bahwa belajar melalui bahan ajar dengan konten budaya memberikan pengalaman belajar yang lebih sehingga peserta didik merasa memiliki nilai-nilai budaya tersebut (Baka, 2019). Upaya memperkuat ketahanan budaya di Indonesia, guru memerlukan bahan ajar kontekstual untuk memberikan pengalaman belajar pada peserta didik (Charlina & Septyanti, 2019). Penggunaan LKPD bermuatan kearifan lokal merupakan penggunaan media belajar yang kontekstual yang bertujuan menciptakan sumber belajar yang layak untuk dipergunakan peserta didik dalam upaya meningkatkan ketahanan budaya lokal daerah melalui peningkatan pemahaman konsep kearifan lokal siswa dan pengalaman belajar siswa dari proses belajar di sekolah.…”
Section: Pendahuluanunclassified
“…From the results of the feasibility assessment by material experts and material experts, it can be concluded that science literacy-based digital teaching materials in terms of feasibility have improvements in order to achieve a product that is very feasible to be applied to learning. In accordance with the research of Charlina et al (2019) validated products require improvement until the developed product is said to be suitable for use in the next stage. The feasibility validation results have a significant influence in improving the products developed (Setiawan et al, 2020).…”
Section: Feasibility Of Science Literacy Based Digital Teaching Mater...mentioning
confidence: 98%
“…Display of the book can be seen in Figure 1. According to Charlina & Septyanti (2019), Validation aims to provide value and determine the feasibility of non-text books prior to field trials (Ilmiawan, 2018).…”
Section: Designmentioning
confidence: 99%